2011
DOI: 10.1136/bjo.2011.203125
|View full text |Cite
|
Sign up to set email alerts
|

No advanced retinopathy of prematurity stages 4 or 5 in a large high-risk German cohort

Abstract: In this very immature high-risk cohort, advanced stages 4 and 5 were avoided throughout 9 years of screening. We suggest three factors that contributed to this outcome: (1) strict adherence to current ROP screening and treatment guidelines; (2) prompt and very dense laser coagulation if necessary; and (3) a specialised neonatal intensive care unit with experience of very immature babies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…In the Canadian study, 14 the earliest onset of Type 1 ROP was 6 weeks chronological age or 32.7 weeks PMA. In the study by Muether et al 15 that included 767 infants 22-35 weeks gestation, no infants required treatment before 8 weeks chronologic age or 33 weeks PMA. Together these studies provide no evidence that current screening guidelines should be changed to accommodate earlier (Type 1 ROP) treatment, although we still have limited data for 22-23 week GA infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Canadian study, 14 the earliest onset of Type 1 ROP was 6 weeks chronological age or 32.7 weeks PMA. In the study by Muether et al 15 that included 767 infants 22-35 weeks gestation, no infants required treatment before 8 weeks chronologic age or 33 weeks PMA. Together these studies provide no evidence that current screening guidelines should be changed to accommodate earlier (Type 1 ROP) treatment, although we still have limited data for 22-23 week GA infants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication from Canada reported the age of onset of Type 1 ROP in a cohort of 214 infants ≤ 27 weeks gestation; 14 this cohort included only 24 infants with Type 1 ROP. A recent publication from a German cohort 15 reported that “No preterm infants required treatment before the 33rd postmenstrual week or 8th postnatal week, respectively”; the age distribution was not reported. We need updated information about the evolution of ROP in a large contemporary cohort to determine when screening must be initiated to capture all infants as Type 1 ROP develops.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the study design, definition of severe ROP, comorbidity of infants, proportion of inborn infants, and disagreement on plus sign may explain the reason (18). As GA at birth decreases, incidence of severe ROP usually increases (10, 11, 13, 14). However, in this study, the incidence of type 1 ROP was not significantly different between 23 and 24 weeks GA groups.…”
Section: Discussionmentioning
confidence: 99%
“…The development of type 1 ROP before 31 weeks PMA was not reported in two recent studies including more than 100 preterm infants born before 25 weeks gestation. In a German cohort study, no preterm infants required treatment before the 33rd postmenstrual week (14). In a Swedish study, ROP at stages 2 and 3 was seen as early as 29.9 and 31.6 weeks, respectively (19, 20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation